183k views
0 votes
18 - 3z = 2z - 6z - 3. x=
(fraction)

User Sashay
by
5.3k points

2 Answers

6 votes

Answer:

If you mean "z" instead of "x", the answer should be -21.

Explanation:

18 - 3z = 2z - 6z - 3

-3z - 2z + 6z = -18 - 3

z = -21

User Dmytro Pishchukhin
by
5.2k points
6 votes

Answer:

-21

Explanation:

18-3z = 2z - 6z -3

18-3z = -4z -3

-3z+4z= -3-18

z=-21

User Praneeth Paruchuri
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.